Pandangan Lulusan Prodi Manajemen Informasi dan Dokumen ProgramPendidikan Vokasi UI Terhadap Pekerjaan di Bidang Perpustakaan dan Kearsipan - Safitri, Dyah (Jurnal Vokasi Indonesia, 2017)
The need for human resources with expertise in managing information is needed. As the amount of arsiparist power with the need for power is far from balanced. The need for librarians is also very high in managing information. The purpose of this research is to know the views of graduates of the 2014 MID program that graduated in 2017 to the profession they will undergo. The study used the online survey method of MID student program class of 2014. The results showed that softskill and hardskill from lecture subject taught to them felt will support their profession forward. From the willingness to work, the majority of respondents choose the archive field because they feel mastered the field. Further education becomes one of the greatest wishes for MID graduate students to earn a bachelor's degree.